APPRAISAL OF THE IN VITRO ANTIBACTERIAL AND ANTIOXIDANT POTENTIAL OF THE LEAF EXTRACTS OF CADABA FRUTICOSA - Lavinya, B. Udhaya; J.L.AKALYA; Srujana, K.S.L.; Sabina, Evan Prince; Devi Rajeswari, V. (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Objective: The aim of the present study is to evaluate the in vitro antimicrobial and antioxidant activities of the leaf extracts of the medicinal plant C. fruticosa. Methods: The antimicrobial activities of the aqueous and methanolic extracts against different bacterial strains were determined by disc diffusion method and compared with that of the standard antibiotic cefotaxime. Determination of the reducing power and 1,1-Diphenyl-2-picryl-hydrazyl (DPPH) radical scavenging activity were carried out on different concentrations of the methanolic extract in order to evaluate the antioxidant potential of C. fruticosa. The total phenolic content of the methanolic extract was measured. Results: The antimicrobial activity of the aqueous extract was found to be lesser compared to that of the methanolic extract. The methanolic extract showed significant antimicrobial and antioxidant activities. Conclusion: From the present study it is evident that the methanolic extract of the leaves of C. fruticosa possesses significant antimicrobial and antioxidant activities. Â  Keywords: Cadaba fruticosa, antimicrobial, antioxidant, DPPH assay